2013
DOI: 10.1038/npp.2013.344
|View full text |Cite
|
Sign up to set email alerts
|

The Knockout of Secretin in Cerebellar Purkinje Cells Impairs Mouse Motor Coordination and Motor Learning

Abstract: Secretin (SCT) was first considered to be a gut hormone regulating gastrointestinal functions when discovered. Recently, however, central actions of SCT have drawn intense research interest and are supported by the broad distribution of SCT in specific neuronal populations and by in vivo physiological studies regarding its role in water homeostasis and food intake. The direct action of SCT on a central neuron was first discovered in cerebellar Purkinje cells in which SCT from cerebellar Purkinje cells was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 46 publications
(84 reference statements)
1
37
0
Order By: Relevance
“…; Zhang et al . ). For the righting reflex assay, each mouse was placed on its back and the time it took the mouse to right itself was measured (Yu et al .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Zhang et al . ). For the righting reflex assay, each mouse was placed on its back and the time it took the mouse to right itself was measured (Yu et al .…”
Section: Methodsmentioning
confidence: 97%
“…; Zhang et al . ). For the negative geotaxis assay, each mouse was placed on a 45 deg wooden inclined plane with its body pointed towards the base of the platform (Mocholi et al .…”
Section: Methodsmentioning
confidence: 97%
“…This finding compliments our previous finding that secretin facilitated EBC when infused into lobulus simplex of cerebellar cortex prior to acquisition sessions 1 -3 (Williams et al 2012). Since secretin is endogenously expressed in PCs in cerebellar cortex (Yung et al 2001;Köves et al 2002;Zhang et al 2014), is released when PCs are Figure 3. Experiment 2: mean + SEM percentage of eyeblink CRs as a function of session for adaptation, acquisition and extinction.…”
Section: Discussionmentioning
confidence: 99%
“…Other research has shown that secretin is expressed in the somatodendritic region of PCs (Yung et al 2001) and its G S -protein coupled receptor is expressed in PCs and basket cells (BCs) (Yung et al 2001;Köves et al 2002;Zhang et al 2014). Secretin release can be induced by depolarization of cerebellar tissue with KCl and this secretin release is inhibited by an L-type or a P/Q-type calcium channel blocker (Lee et al 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation